2002
DOI: 10.1063/1.1488925
|View full text |Cite
|
Sign up to set email alerts
|

An accurate semiclassical method to predict ground-state tunneling splittings

Abstract: A new method for calculating the ground-state tunneling splitting is presented. It is based on the semiclassical theory including recently derived corrections and it is the first method, which explicitly takes into account the whole conformational space between the minima and the transition state. The density-functional theory is used to determine the qualitative shape of the potential energy surface ͑PES͒ and high level ab initio calculations provide information about the stationary points. With a dual level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 73 publications
0
40
0
Order By: Relevance
“…In principle, tunneling paths must be those that give the minimum action integral, and turning points should satisfy a condition that the momentum in a direction of tunneling is equal to zero. In general, however, it is difficult to find such an optimal tunneling path in multidimensional configuration space, [22][23][24] and thus, one should determine the way to define an appropriate tunneling path prior to AIMD simulations. In the next section, we demonstrate the way to determine the turning point and the tunneling path for two illustrative applications.…”
Section: The Semiclassical Tunneling Methodsmentioning
confidence: 99%
“…In principle, tunneling paths must be those that give the minimum action integral, and turning points should satisfy a condition that the momentum in a direction of tunneling is equal to zero. In general, however, it is difficult to find such an optimal tunneling path in multidimensional configuration space, [22][23][24] and thus, one should determine the way to define an appropriate tunneling path prior to AIMD simulations. In the next section, we demonstrate the way to determine the turning point and the tunneling path for two illustrative applications.…”
Section: The Semiclassical Tunneling Methodsmentioning
confidence: 99%
“…[23][24][25] It has been shown that the quantum mechanical tunneling is not restricted to the motion of the hydrogen atom alone but is coupled to the motion of the heavy backbone atoms. 21,26,27 Thus, the proton transfer in malonaldehyde is a truly multidimensional tunneling process. Experimentally, the ground state tunneling splitting has been determined very accurately 5,28 to be 21.583 138 29 ± ͑63͒ cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…They also successfully applied their semiclassical method for finding the tunneling path to (HF) 2 and TRN [93], where the 7.2 kcal mol -1 quantum chemistry barrier for TRN is 50 to 100% lower than the barriers used for the computations on TRN discussed above. It is similar to the MP4/GEN results (footnote b of Table 1.3) used in the following discussion of the tautomerization of S 0 TRN that is based on an examination of the computed and spectroscopic data set for TRN(OH) and TRN(OD) [34][35][36]86].…”
Section: Coherent Tunneling Phenomena In Tropolonementioning
confidence: 99%